Additive manufacturing method and different welding applications - Karayel, Elif; Bozkurt, Yahya (Journal of materials research and technology, 2020)
Additive manufacturing (AM) technology, in other words “layered manufacturing” or “3D printer technology” has been developing rapidly in recent years. Unlike the traditional manufacturing method (TM), the working principle of AM technology is to create layer-based production by deposition the layers on top of each other. Owing to its advantages such as material saving, lower cost, the ability to produce parts without the need for molds and the design flexibility in complex shaped parts, it has brought a breath of fresh air to the areas where it is used primarily medical, aerospace and automotive. However, the parts produced by AM method have dimensional limitations. According to recent studies, in order to eliminate this problem, metal materials produced with AM can be combined with commonly used by different welding methods so that large parts can be obtained. In this study, these welding methods are explained and recent researches are examined. AM technology and methods are introduced. The usage areas of the method are described. In addition, the welding parameters and the effects of this new method on the mechanical properties and microstructures are investigated.